(untitled) (World Bulletin of Social Sciences, 2021)
The article highlights to improve the quality and professional competence of teachers working in non-governmental educational institutions and analyzes the development of modern approaches and principles. The contents of developed countries of the world, non-governmental educational institutions as one of the focuses of the modernization of the competitive approach to the issues